ANALISIS PREDIKSI KEBANGKRUTAN BANK PERKREDITAN RAKYAT - , Kuntari Setyorini ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aimed to examine whether the financial ratios included in CAMEL facorts on Bank Rating (TKS, the capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR) and return to assets (ROA) can be used to predict the bankruptcy of a Indonesian Rural Bank (BPR). The method used in this research is the statistical discriminant analysis to study variables consists of 2 (two) dependent variable shaped non-metrical/category with 2 (two) categories, namely the bankrupt bank dan the non bankrupt bank with 4 (four) independent variable shaped metrics/numbers, in the form of financial ratios. The financial ratios used are CAR, NPL, LDR and ROA. While the number of samples in this research are 23 Indonesian Rural Bank (BPR) that have been liquidated from year 2006 until 2011 and 230 samples BPR located in Jakarta, Bogor, Depok, Tangerang, Bekasi and Banten area that still in operation until December 31st, 2011. The results showed that all the independent variables used in this research, the ratio of CAR, NPL, LDR, and ROA is significantly able to differ the bankrupt bank and the non bankrupt bank with the significant value above than 0,05. In addition, the level of accuracy for the prediction of bank bankruptcy one year prior to bankruptcy was 93,28% or higher than the data 2 (two) years before the bankruptcy was 87,75%. Thus CAR, NPL, LDR & ROA ratio in the year before the bankruptcy has a significant impact on the bankâs collapse.